2020
DOI: 10.1371/journal.pone.0236801
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of adherence, retention, and transition patterns of adolescents living with HIV in Nigeria

Abstract: Introduction Adherence to antiretroviral therapy (ART) and retention in treatment programs are required for successful virologic suppression and treatment outcomes. As the number of adolescents living with HIV continues to increase globally, more information about adherence and retention patterns during and through transition from child- to adult-centered care is needed to ensure provision of a high level of care and inform development of targeted interventions to improve patient outcomes in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…Several studies have demonstrated suboptimal viral suppression in children and adolescents in high and lowresource settings. A study conducted in Nigeria, observed that the viral load suppression rates through adolescence and post-transition were only 55.6-64.0% [10]. Another study in Cambodia showed a relatively low viral suppression rate amongst adolescents compared to the adult population groups, with the viral suppression rate at 76.8% and 90% respectively [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated suboptimal viral suppression in children and adolescents in high and lowresource settings. A study conducted in Nigeria, observed that the viral load suppression rates through adolescence and post-transition were only 55.6-64.0% [10]. Another study in Cambodia showed a relatively low viral suppression rate amongst adolescents compared to the adult population groups, with the viral suppression rate at 76.8% and 90% respectively [11].…”
Section: Introductionmentioning
confidence: 99%
“…2 Globally, HIV is the second leading cause of death among adolescents. 3 It is also estimated that over 80% of adolescents living with HIV in the world reside in sub-Saharan Africa. 34 In Africa, this group constitutes a third of the population with Zimbabwe, Nigeria, and South Africa bearing the burden.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 However, attaining and sustaining the HIV treatment endpoints, requires not less than 95% continuous adherence to ART. 3,15,16 Failure of which results in the selection of resistant strains of the virus, which leads to disease progression, reduction of future therapeutic options, and increased risk of HIV transmission due to high viral load (VL). Adolescents have been generally identified as having poor adherence to ART and hence poorer outcomes compared to their adult counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in low and middle income countries (LMIC) have investigated the transition to adult care of adolescents with chronic medical conditions such as sickle cell disease and asthma [23][24][25]. A few studies involving ALHIV have focused on transition readiness assessment [26], patient and healthcare providers' perspectives on transition and some have investigated transition programs [12,27]. Very little is known about caregiver perspective on transitioning ALHIV from paediatric HIV care to adult services especially in Nigeria.…”
Section: Introductionmentioning
confidence: 99%